2005
DOI: 10.1002/dys.310
|View full text |Cite
|
Sign up to set email alerts
|

The subtypes of developmental dyslexia in Chinese: evidence from three cases

Abstract: This study investigated subtypes of developmental dyslexia in Chinese by assessing three cases of Chinese dyslexic children. A battery of screening measures, a character naming and meaning task, and metalinguistic awareness tasks were administered to each child. One of the three children demonstrated characteristics of developmental surface dyslexia, and the other two showed characteristics of developmental deep dyslexia. Moreover, the children's reading problems were found to be specifically related to their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 45 publications
3
42
0
1
Order By: Relevance
“…However, both of these hemispheres are not functionally equal and that may explain the differences between people with dyslexia (Lavidor et al 2006). In addition, differences in the locus of cerebellar impairment may be responsible for subtypes of dyslexia, such as developmental surface and developmental deep dyslexia (Shu et al 2005;Nocolson and Fawcett 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, both of these hemispheres are not functionally equal and that may explain the differences between people with dyslexia (Lavidor et al 2006). In addition, differences in the locus of cerebellar impairment may be responsible for subtypes of dyslexia, such as developmental surface and developmental deep dyslexia (Shu et al 2005;Nocolson and Fawcett 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Specific problems in subgroups of dyslexic children need to be identified (Shu et al, 2005). Knowledge in more than the native language has long been a necessity in many parts of the world, and is of increasing importance today.…”
Section: Discussionmentioning
confidence: 99%
“…The data are consistent with the idea that cognitive strategies for reading development tune the cortex . A recent detailed study on the different reading problems in three dyslexic Chinese children indicates that the prevalence of subgroups of dyslexia in Chinese children needs to be further studied (Shu et al, 2005).…”
Section: Disorders In Japanese and Chinesementioning
confidence: 99%
“…Impairment to the lexical semantic pathway will result in acquired surface dyslexia, while impairment to the nonsemantic pathway results in deep dyslexia. In a case study, Shu, Meng, Chen, Luan, and Cao, (2005) reported two types of dyslexic children, surface and deep, who showed the impairment in different pathways. Two dyslexic children, Child-L and Child-J, were tested by a word recognition task, in which they were asked to name a character and then to compose a compound word based on the target character.…”
Section: The Characteristics and Core Deficits Of Chinese Children Wimentioning
confidence: 99%